The relationship between urine heat shock protein 70 and congenital anomalies of the kidney and urinary tract: UTILISE study - Aksu, Bagdagul; Afonso, Alberto Caldas; Akil, Ipek; Alpay, Harika; Atmis, Bahriye; Aydog, Ozlem; Bakkaloglu, Sevcan; Bayazıt, Aysun Karabay; Bayram, Meral Torun; Bilge, Ilmay; Bulut, Ipek Kaplan; Cetinkaya, Ayse Pinar Goksu; et al. (Frontiers in Urology, 2024)
Background: Congenital anomalies of the kidney and urinary tract (CAKUT) are defined as structural malformations of the kidney and/or urinary tract. Heat shock proteins (HSPs) are expressed in the kidney in response to cellular changes, such as thermal, hemodynamic, osmotic, inflammatory, and mechanical stresses. This study aimed to assess uHSP70 levels during acute urinary tract infections (UTI) and non-infection periods in patients with CAKUT, and to evaluate whether uHSP70 is elevated in CAKUT subtypes. Methods: Among patients with CAKUT, 89 patients with UTI (CAKUT-A), 111 without UTI (CAKUT-B), and 74 healthy children were included in the study. uHSP70 levels were measured using enzyme-linked immunosorbent assay (ELISA). Results: uHSP70 level was significantly higher in the CAKUT-A group than in the CAKUT-B and healthy control groups (p < 0.0001). Moreover, the level of uHSP70 was significantly higher in the CAKUT-B group than in the control group (p < 0.0001), but was not different between the CAKUT subtypes (p > 0.05). Conclusions: Urine HSP70 can also be used to predict UTI in patients with CAKUT. Moreover, uHSP70 levels were higher in children with CAKUT during the non-infectious period than in healthy controls. This suggests that children with CAKUT are at risk of chronic non-infectious damage.